Fostering Students’ Reading Comprehension Ability through Directed Reading Thinking Activities (DRTA) Strategy - Yuni Putri Utami; Sugirin Sugirin (Journal of English Language Teaching and Linguistics, 2019)
The current curriculum school reform in Indonesia supported the students to be a critical thinker in the sense that the students become a centered of teaching instruction in the school life. This changing becomes a new demand for the teacher as an educator to facilitate their learners with teaching aids practices that adjust learners to be actively participate in the classroom. Thus, this study used Directed Reading Thinking Activities (DRTA) to reveal the effectiveness of this strategy on the students’ reading comprehension teaching. A quasi-experimental research design with pretest and posttest was used in this study. Two classes were randomly selected as the sample of this research. They are class 8C which used Directed Reading Activities (DRA) as the control group, while class 8H becomes the experimental group which used Directed Reading Thinking Activities (DRTA). Independent and dependent (paired) sample t-tests were used to analyze the data. The research finding showed: 1) there were no significant differences of posttest score among the students taught by using DRTA and those taught by using DRA strategy in reading comprehension teaching, 2) there were significant effects of using DRTA in reading comprehension teaching for grade eight students. DRTA strategy was believed to give more contribution (82%) than DRA strategy which contributed only 77%. In conclusion, DRTA was effective strategy in reading comprehension teaching.